An Ant Colony Optimization to Optimize Selection Method of Wavelet Packet Basis - ZOU Fang-hao; ZHANG Han; MENG Liang; XU Tong-le; SU Yuan-hao (Journal of Harbin University of Science and Technology, 2022)
In order to study the poor effect of the existing best basis selection algorithm in reducing the noise of weak fault signals and the difficulty of determining the terminal node, according to the ant colony algorithm and wavelet packet related theories, the factors affecting the selection of the wavelet packet basis are analyzed, and the selection rules are analyzed.After redefining and combining the global optimization ability of ant colony algorithm to optimize the newly defined terminal node coordinate set and decomposition level, a wavelet packet basis optimization method based on ant colony algorithm is given.Compared with the traditional best basis selection algorithm, the convergence performance and distribution performance of the new method are enhanced by 12.5%. In the process of reducing the noise of the weak fault signal of the bearing, the signal-to-noise ratio after processing is increased by 46.7%, and the root mean square error is reduced by 20.4%, verifying the effectiveness and superiority of the new method.